Development and validation of a method for the determination of folic acid in different pharmaceutical formulations using derivative spectrophotometry - Ribeiro, Marcos Vinícius de Moura [UNESP]; Melo, Ingrid da Silva; Lopes, Francisco das Chagas da Costa; Moita, Graziella Ciaramella (FapUNIFESP (SciELO), 2016)
Folic acid is a B complex water-soluble vitamin that is essential to humans, and its deficiency can cause problems including congenital malformations in the fetus as well as heart disease. Most countries affected by diseases associated with a lack of folic acid now supplement foods with the vitamin. There is therefore a need for the development of new analytical procedures able to determine folic acid present in different matrices. This work describes the development of zero order and first order derivative spectrophotometric methods for the determination of folic acid in different pharmaceutical formulations, using 0.1 mol L-1NaOH as solvent. The methods are shown to be simple, selective, and robust. Good linearity was achieved, with correction coefficients ≥0.9996 and limits of detection and quantification ranging from 0.64 to 0.75 and from 1.80 to 2.85 mg L-1, respectively. Recoveries of 98-104% were obtained in accuracy tests, and precision (as RSD) was between 0.2 and 4.8%. The methods can be used in routine analyses for quality control purposes, offering an alternative to the procedures already reported in the literature.
Keywords: Folic acid/formulations/derivative spectrophotometry; Folic acid/pharmaceutical formulations; Folic acid/pharmaceutical formulations/validation method